2020
DOI: 10.1186/s13256-020-02576-6
|View full text |Cite
|
Sign up to set email alerts
|

Gastric carcinoma and renal cell carcinoma as an atypical presentation of multiple primary malignancies: a case report and review of the literature

Abstract: Background Gastric carcinoma (GC) with second primary malignancy (SPM) is the most frequent combination within the multiple primary malignancies (MPM) group. The presentation of a GC associated with a synchronized SPM in the kidney is extremely rare and unusual. This study presents a rare case of synchronous tumors, describes the main associated risk factors, and emphasizes the need to rule out SPM. Main body We present the case of a 63-year-old Hispanic woman with a history of smoking, weight loss, and gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 39 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…Thus far, most descriptions of MPMs in patients with GC (i.e., GCM) have been provided in case reports. [24][25][26] Therefore, the present study used a public database (SEER) for analysis of GCM. The database contained 29,791 cases of GCM between 2010 and 2019, which was sufficient for a large-scale analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, most descriptions of MPMs in patients with GC (i.e., GCM) have been provided in case reports. [24][25][26] Therefore, the present study used a public database (SEER) for analysis of GCM. The database contained 29,791 cases of GCM between 2010 and 2019, which was sufficient for a large-scale analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we observed two different types of malignant tumors in a female patient: adenocarcinoma of the stomach and clear cell renal carcinoma. Upon reviewing the literature, we found that synchronous renal cell neoplasms are extremely rare, with a prevalence of 0.11–0.37% [ 8 ]. Additionally, the male-to-female ratio is 2:1 and most renal tumors are discovered incidentally through imaging studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Upon reviewing the literature, we found that synchronous renal cell neoplasms are extremely rare, with a prevalence of 0.11–0.37% [ 8 ]. Additionally, the male-to-female ratio is 2:1 and most renal tumors are discovered incidentally through imaging studies [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations